A large pyrene-fused N-heteroacene: fifteen aromatic six-membered rings annulated in one row. Issue 55 (26th June 2017) - Wang, Zilong; Gu, Peiyang; Liu, Guangfeng; Yao, Huiying; Wu, Yishi; Li, Yongxin; Rakesh, Ganguly; Zhu, Jia; Fu, Hongbing; Zhang, Qichun
Abstract : A novel nitrogen-rich N-heteroacene with 15 linearly-fused aromatic six-membered rings has been synthesized and fully characterized. Abstract : Here, we present our recent progress on the synthesis, crystal structure, physical properties and DFT calculations of a novel large pyrene-fused N-heteroacene (15RINGS ) with 15 aromatic six-membered rings linearly fused in one row. The long conjugated backbone (more than 35 Å) of15RINGS possesses a dual-bending feature (the bending angle is about 13.2°).